Answer:
(a) t = 1.14 s
(b) h = 0.82 m
(c) vf = 7.17 m/s
Step-by-step explanation:
(b)
Considering the upward motion, we apply the third equation of motion:
![2gh = v_f^2 - v_i^2](https://img.qammunity.org/2022/formulas/physics/high-school/sjnbmxdyqrgekez3llhddqmh16huktghy2.png)
where,
g = - 9.8 m/s² (-ve sign for upward motion)
h = max height reached = ?
vf = final speed = 0 m/s
vi = initial speed = 4 m/s
Therefore,
![(2)(9.8\ m/s^2)h = (0\ m/s)^2-(4\ m/s)^2\\](https://img.qammunity.org/2022/formulas/physics/college/9npy5687sdvtktkv1fv7lp0p305lyjddc1.png)
h = 0.82 m
Now, for the time in air during upward motion we use first equation of motion:
![v_f = v_i + gt_1\\0\ m/s = 4\ m/s + (-9.8\ m/s^2)t_1\\t_1 = 0.41\ s](https://img.qammunity.org/2022/formulas/physics/college/h1wz04h52708437mqk9le5fd08htij6wu7.png)
(c)
Now we will consider the downward motion and use the third equation of motion:
![2gh = v_f^2-v_i^2](https://img.qammunity.org/2022/formulas/physics/college/g9hittskjf302mdwb88vvdmhbds6j6ahp8.png)
where,
h = total height = 0.82 m + 1.8 m = 2.62 m
vi = initial speed = 0 m/s
g = 9.8 m/s²
vf = final speed = ?
Therefore,
![2(9.8\ m/s^2)(2.62\ m) = v_f^2 - (0\ m/s)^2\\](https://img.qammunity.org/2022/formulas/physics/college/sjriqhpn60929qdru635nnvzawoyx2t6tf.png)
vf = 7.17 m/s
Now, for the time in air during downward motion we use the first equation of motion:
![v_f = v_i + gt_1\\7.17\ m/s = 0\ m/s + (9.8\ m/s^2)t_2\\t_2 = 0.73\ s](https://img.qammunity.org/2022/formulas/physics/college/xu06tf33rak27j8ruv6issbye271q2oi8k.png)
(a)
Total Time of Flight = t = t₁ + t₂
t = 0.41 s + 0.73 s
t = 1.14 s